Nursing of a patient undergoing continuous renal replacement therapy for chronic renal failure (1例慢性肾衰竭患者连续性肾脏替代治疗及护理体会) - XU Juan (许娟); WANG Yaru (王亚茹) (中西医结合护理, 2023)
This paper summarized the nursing management for a patient undergoing bedside continuous renal replacement therapy (CRRT) for acute exacerbation of chronic renal failure. Key issues of nursing including hemofiltration catheter maintenance, illness condition observation, psychological care and complications prevention and control. Clinical symptoms such as limb edema and dyspnea were successful relieved after implementation of CRRT and related nursing interventions, and patient had completed the following treatment. (本文回顾1例慢性肾衰竭急性加重期患者行床旁连续性肾脏替代治疗的效果, 总结护理经验, 包括血液滤过置管护理、病情观察、心理护理、并发症护理等。通过床旁连续性肾脏替代治疗治疗后患者水肿、喘憋等临床症状明显好转。)